Green spaces and mortality due to cardiovascular diseases in the city of Rio de Janeiro - Ismael Henrique da Silveira; Washington Leite Junger (Revista de Saúde Pública, 2018)
ABSTRACT OBJECTIVE Investigate the association between exposure to green spaces and mortality from ischemic heart and cerebrovascular diseases, and the role of socioeconomic status in this relationship, in the city of Rio de Janeiro, Brazil. METHODS Ecological study, with the census tracts as unit of analysis. This study used data from deaths due to ischemic heart and cerebrovascular diseases among residents aged over 30 years, from 2010 to 2012. Exposure to green was estimated using the Normalized Difference Vegetation Index based on satellite images. The associations between exposure to green spaces and mortality rates due to ischemic heart and cerebrovascular diseases, standardized by gender and age, were analyzed using conditional autoregressive models, adjusted for the density of light and heavy traffic routes, pollution proxy, and by the socioeconomic situation, measured by the Social Development Index. Analyzes stratified by socioeconomic levels were also carried out, given by the tertiles of the Social Development Index. RESULTS Among the greener sectors, with a Normalized Difference Vegetation Index above the third quartile, the reduction in mortality due to ischemic heart disease was 6.7% (95%CI 3.5–9.8) and cerebrovascular was 4.7% (95%CI 1.2–8.0). In the stratified analysis, the protective effect of green spaces on ischemic heart disease mortality was observed among the greenest sectors of all strata, and it was higher for those with a lower socioeconomic level (8.6%, 95%CI 1.8–15.0). In the case of mortality due to cerebrovascular diseases, the protective effect was verified only for the greenest sectors of the lowest socioeconomic level (9.6%, 95%CI 2.3–16.5). CONCLUSIONS Mortality rates for ischemic heart and cerebrovascular diseases are inversely associated with exposure to green spaces when controlling socioeconomic status and air pollution. The protective effect of green spaces is greater among the tracts of lower socioeconomic level.